2021
DOI: 10.3390/toxins13120874
|View full text |Cite
|
Sign up to set email alerts
|

FumDSB Can Reduce the Toxic Effects of Fumonisin B1 by Regulating Several Brain-Gut Peptides in Both the Hypothalamus and Jejunum of Growing Pigs

Abstract: Fumonisin B1 (FB1) is the most common food-borne mycotoxin produced by the Fusarium species, posing a potential threat to human and animal health. Pigs are more sensitive to FB1 ingested from feed compared to other farmed livestock. Enzymatic degradation is an ideal detoxification method that has attracted much attention. This study aimed to explore the functional characteristics of the carboxylesterase FumDSB in growing pigs from the perspective of brain–gut regulation. A total of 24 growing pigs were divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…FUM zyme ® is designed for use in animal feed to mitigate the toxic effects of fumonisins, thereby improving animal health and performance. Li et al screened another carboxylesterase FumDSB from the genus Sphingomonadales bacterium from GenBank based on a sequence-similarity search using BLASTp analysis [ 19 ], and found that the addition of FumDSB can reduce the anorexia effects of FB1 by regulating several brain–gut peptides in both the hypothalamus and the jejunum of growing pigs [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…FUM zyme ® is designed for use in animal feed to mitigate the toxic effects of fumonisins, thereby improving animal health and performance. Li et al screened another carboxylesterase FumDSB from the genus Sphingomonadales bacterium from GenBank based on a sequence-similarity search using BLASTp analysis [ 19 ], and found that the addition of FumDSB can reduce the anorexia effects of FB1 by regulating several brain–gut peptides in both the hypothalamus and the jejunum of growing pigs [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…7,10 Moreover, the alteration of gut microbiota composition and brain− gut peptide secretion proved to be new approaches to alleviate the intestinal toxicity of FB 1 . 11,12 However, the underlying mechanism and regulatory means of FB 1 -induced intestinal inflammatory injury have not been clarified in detail, which need further study.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that exposure to FB 1 led to the inhibition of intestinal epithelial cell proliferation, villus injury, intestinal barrier disruption, and inflammatory response in vivo and in vitro. , Therefore, it is necessary to explore the intestinal injury caused by FB 1 and its potential mechanism. Recent studies have elucidated that FB 1 exposure triggered intestinal injury via activating nuclear xenobiotic receptors, inducing ionic homeostasis imbalance and cytochrome P450 system disturbance in mice. , Moreover, the alteration of gut microbiota composition and brain–gut peptide secretion proved to be new approaches to alleviate the intestinal toxicity of FB 1 . , However, the underlying mechanism and regulatory means of FB 1 -induced intestinal inflammatory injury have not been clarified in detail, which need further study.…”
Section: Introductionmentioning
confidence: 99%